Leis de escala para o mapa padrão dissipativo - Francisco, Caio Henrique [UNESP] (2015)
We considered in this work the characterisation of some scaling properties for the dynamics of the dissipative standard map. The map is described by the use of two dynamical variables, the action I, and the angle θ. The model is also characterised by two control parameters k and γ. The parameter k controls the intensity of the nonlinearity while γ describes the amount of dissipation. For γ= 0 the system is non dissipative. Depending on the parameter k, the phase space is mixed containing either periodic islands, invariant curves and chaos. For k > 0:9716..., the invariant spanning curves are all destroyed allowing the action to diffuse unbounded in the phase space. On the other hand when γ= 0, the system is dissipative and attractors appear in the phase space...